Mo. Const. of 1875 art. II, § 17 - (:unkn) unknown (My University, 1875)
The right of no citizen to keep and bear arms in defense of his home, person, and property, or in aid of the civil power, when thereto legally summoned, shall be called into question. But nothing herein is intended to justify the practice of wearing concealed weapons.
Keywords: GUARANTEED RIGHT